From SPARC_LAB to EuPRAXIA@SPARC_LAB - Riccardo Pompili; Enrica Chiadroni; Alessandro Cianchi; Massimo Ferrario; Alessandro Gallo; Vladimir Shpakov; Fabio Villa (Instruments, 2019)
Following the promising results obtained at the SPARC_LAB test-facility in Frascati (Italy), we have recently submitted a proposal to develop a new facility driven by a plasma accelerator module for extended and user-oriented applications. The new multi-disciplinary user-facility will be equipped with a soft X-ray Free Electron Laser (FEL) operating with energies larger than 1 GeV. This design study is performed to be fully compatible with the EuPRAXIA design study. Here, the latest layout and beam parameters are presented.